2022
DOI: 10.3390/children9050650
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in the Anthropometric and Physical Fitness Characteristics of Young Soccer Players: A Cross-Sectional Study

Abstract: Considering that most professional academies seek to optimize the early detection and physical development of their younger players, the purpose of this study was to examine the anthropometric and physical fitness characteristics in a large cross-sectional sample of youth soccer players in Eastern Europe, starting from a very young age during their in-season period. Three hundred and thirteen soccer players (n = 313), grouped into eight age categories, participated in the study. On the basis of chronological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
(52 reference statements)
1
4
0
Order By: Relevance
“…Previous studies reported that the onset of accelerated height growth is around 10–12 years of age ( 41 ). The data on height and weight coincide with other studies performed on soccer ( 42 ), padel ( 43 ) and TT ( 33 ) players. These differences are directly related to sexual dimorphism between males and females ( 44 , 45 ).…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies reported that the onset of accelerated height growth is around 10–12 years of age ( 41 ). The data on height and weight coincide with other studies performed on soccer ( 42 ), padel ( 43 ) and TT ( 33 ) players. These differences are directly related to sexual dimorphism between males and females ( 44 , 45 ).…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, it can be hypothesized that there is a significant influence of age on strength in boys ( Parpa and Michaelides, 2022 ), and that, consequently, increases in measured performance values with enhanced age may be attributed to a higher relative maximum strength level due to pubescence, whereas, in female soccer players, a decrease in relative strength with increased age can be observed ( Emmonds et al, 2020 ). There would appear to be sex-related factors that influence explosive strength performance.…”
Section: Discussionmentioning
confidence: 99%
“…Sprint performance was assessed using a maximal 30 m sprint according to the methods described by previous investigators [ 26 ]. Sprint times were recorded at 10, 20, and 30 m, but only the 30 m sprinting time was used for the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The players’ agility was evaluated with the T-test, which involves forward, backward, and lateral running. The test required four cones arranged into a T-shape according to the methods described by previous investigators [ 26 ]. The first and second cones were placed 9.14 m apart, while cones three and four were placed 4.57 m from either side of the second cone.…”
Section: Methodsmentioning
confidence: 99%